(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Andrianov T. V. Psychological and pedagogical aspects of formation of a healthy lifestyle in the structure of the physical professional-applied preparation of future teachers. The article is devoted to the problem of formation of a healthy lifestyle in the structure of the physical professionally-applied training that affect the accumulation of specific knowledge, skills, interests, motives. An attempt is made to explore the main components of professional orientation of future teachers of physical education.